Microservices with Clojure : Develop event-driven, scalable, and reactive microservices with real-time monitoring. - Kumar, Anuj (Packt Publishing, 2018)
Chapter 6: Introduction to Pedestal; Pedestal concepts; Interceptors; The interceptor chain; Importance of a Context Map; Creating a Pedestal service; Using interceptors and handlers; Creating routes; Declaring routers; Accessing request parameters; Creating interceptors; Handling errors and exceptions; Logging; Publishing operational metrics; Using chain providers; Using server-sent events (SSE)Â ; Creating interceptors for SSE; Using WebSockets; Using WebSocket with Pedestal and Jetty; Summary; Chapter 7: Achieving Immutability with Datomic; Datomic architecture.